2017
DOI: 10.1371/journal.pone.0185560
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction model for adenoma detection during screening and surveillance colonoscopy with comparison to actual adenoma detection rates

Abstract: ObjectiveThe adenoma detection rate (ADR) varies widely between physicians, possibly due to patient population differences, hampering direct ADR comparison. We developed and validated a prediction model for adenoma detection in an effort to determine if physicians’ ADRs should be adjusted for patient-related factors.Materials and methodsScreening and surveillance colonoscopy data from the cross-sectional multicenter cluster-randomized Endoscopic Quality Improvement Program-3 (EQUIP-3) study (NCT02325635) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In literature, conflicting results are reported regarding the association between ASA I vs. ASA II and polyp detection. [15,22,26] This study discloses several new case-mix factors to be associated with higher CIR, higher ABPR and higher PDR and confirms the association of earlier described case-mix factors with these outcomes. Adjustment for age, sex, ASA classification and indication influences the interpretation of performance variation between endoscopy centres.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In literature, conflicting results are reported regarding the association between ASA I vs. ASA II and polyp detection. [15,22,26] This study discloses several new case-mix factors to be associated with higher CIR, higher ABPR and higher PDR and confirms the association of earlier described case-mix factors with these outcomes. Adjustment for age, sex, ASA classification and indication influences the interpretation of performance variation between endoscopy centres.…”
Section: Discussionsupporting
confidence: 85%
“…This association remained statistically significant after adjusting for sex and age in multivariable analysis. In the literature, conflicting results are reported regarding the association between ASA I vs. ASA II and polyp detection [15,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although ADR represents the most robust quality indicator of colonoscopy, it still has its own weaknesses[28-30] and thus a plethora of other quality indicators are also used in order to ameliorate the limitations of ADR. Among these metric quality indicators, adenoma miss rates (AMR) has been used extensively in tandem studies, as it is consistent to the back-to-back study design[31].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 41 studies appraised, 10 showed an overall unclear risk of bias [36][37][38][39][40][41][42][43][44], while 30 exhibited an overall high risk of bias . Interestingly, only one study emerged with an overall low risk of bias [76] (Figure 3).…”
Section: Risk Of Bias and Applicability Of The Included Studiesmentioning
confidence: 99%
“…There are two main categories of risk models for predicting CRC or AN based on their predictor features: (1) conventional risk model, which uses known and well-established risk factors for CRC; and (2) composite model, which combines well-established risk factors with more advanced features, such as test/laboratory findings and genetic factors. Among the 41 included studies, we identified 22 original conventional risk models, [36][37][38]40,45,48,50,51,53,54,58,59,61,[63][64][65][67][68][69][70]72,74] and 13 composite models [39,[41][42][43][44]47,56,57,62,71,73,75,76]. Of these, three conventional risk models have undergone external validation in separate studies: (1) the Asia-Pacific Colorectal Screening (APCS) model [45], validated in four other studies [46,49,66,70];…”
Section: Characteristics Of Risk Prediction Models For Crcmentioning
confidence: 99%